Por un intento de subversión interpretativa: Una crítica decolonial a la forma de producir conocimiento social - Ortecho, Mariana Jesus (2014)
This work offers from a triadic semiotics perspective, a set of reflections that aims to contribute to the field of Critical Epistemologies, from a decolonial position specifically. So, from integrating these two theoretical perspectives, a number of questions are formulated to the dominant systems of representation in the field of Social and Human Sciences. The central purpose of the text is focused on identifying and reporting the correlation between some epistemological features positivists -allegedly obsolete and outdated in contemporary scientific work- and certain semiotic characteristics which are considered legitimate in the process of building and communicating social knowledge. Finally, we try to outline a singular methodological route, which starts from the characterization of those representational resources which constitute the gnoseological alternatives that would be necessary to effectively address that invitation, made from the Critical Epistemologies, to retrieve elements from popular wisdom.